Non-accidental trauma in the setting of hemophilia A – A case report - Kameron Williamson; Thomas Weber; Meggan Goodpasture; Amanda Blair (Trauma Case Reports)
Hundreds of thousands of children are victims of non-accidental trauma each year. Its presentation can vary, and it may be difficult to recognize. However, due to its increased risk for fatality, it is imperative that physicians are aware and receptive to the signs of non-accidental trauma to assist with early detection. In a similar fashion, bleeding disorders vary in their presentations and their severity. They also have the potential to occur in the setting of non-accidental trauma, further complicating the diagnosis, increasing morbidity, and mortality. Due to this, suspicion and evaluation for non-accidental trauma should be followed by a bleeding disorder work-up. This case follows a child with undiagnosed Hemophilia-A in the setting of suspected non-accidental trauma. It not only highlights the variation of presentations seen with these ailments but demonstrates the importance of evaluating for comorbidities in highly fatal conditions.